2019
DOI: 10.1016/j.amepre.2018.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Urban–Rural Differences in Older Adult Depression: A Systematic Review and Meta-analysis of Comparative Studies

Abstract: Context: Depression among older adults (≥age 60) is a problem that could be exacerbated by global trends in urbanization and population aging. The study purpose was to assess whether urban, relative to rural, residence is associated with depression among older adults and whether associations differ in countries with developed versus developing economies.Context: Depression among older adults (aged 60 years or older) is a problem that could be exacerbated by global trends in urbanization and population aging. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
103
3
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(121 citation statements)
references
References 82 publications
11
103
3
4
Order By: Relevance
“…For example, three US-based studies included in a recent meta-analysis suggested lower prevalence of depression among rural versus urban older adults. 12 However, other recent US studies have revealed increasing rates of suicide 5,6,50 and alcohol-related and drug-related deaths 2,4 in rural and sparsely populated regions, suggesting that mental health outcomes may disproportionately burden these areas. Our results add to this growing literature on geographic health disparities by suggesting that the prevalence of elevated depressive symptoms may be higher among participants who lived in the rural United States during childhood.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…For example, three US-based studies included in a recent meta-analysis suggested lower prevalence of depression among rural versus urban older adults. 12 However, other recent US studies have revealed increasing rates of suicide 5,6,50 and alcohol-related and drug-related deaths 2,4 in rural and sparsely populated regions, suggesting that mental health outcomes may disproportionately burden these areas. Our results add to this growing literature on geographic health disparities by suggesting that the prevalence of elevated depressive symptoms may be higher among participants who lived in the rural United States during childhood.…”
Section: Discussionmentioning
confidence: 97%
“…Aspects of geographic context that affect mental health may differ across both context (country) and time (birth cohorts and life course period of exposure). For example, three US‐based studies included in a recent meta‐analysis suggested lower prevalence of depression among rural versus urban older adults . However, other recent US studies have revealed increasing rates of suicide and alcohol‐related and drug‐related deaths in rural and sparsely populated regions, suggesting that mental health outcomes may disproportionately burden these areas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of depression in Turkey was reported to be 4.4%, and this ratio was observed to be approximately 8% in adult women and 5.5% in men (26). In a meta-analysis, it was found that the depression rate in developed countries was higher in urban areas than in rural areas and that there was no difference between rural and urban areas in developing countries (27).…”
Section: Discussionmentioning
confidence: 99%